Strategi Pengembangan Objek Wisata Tongkonan Papa Batu Di Lembang Banga’ Kecamatan Rembon Kabupaten Tana Toraja - Abedneigo Carter Rambulangi; Isak Pasulu; Elisabet Pali; Jemi Pabisangan Tahirs; Liandro Doke (CV. Ulil Albab Corp, 2024)
This research aims to find out strategies that can be used to develop the Tongkonan Papa Batu tourist attraction. The results found that from the overall analysis of the data obtained, that in developing the Tongkonan Papa Batu tourist attraction, several new methods are needed in efforts to improve and manage the Tongkonan Papa Batu tourist attraction, such as building facilities at the Tongkonan Papa Batu tourist attraction, improving road access. towards the location and environmental maintenance of tourist attractions so that in the future the Tongkonan Papa Batu tourist attraction becomes the tourist destination of choice for tourists.